المساهمة في دراسة الخصائص الفیزیوكمیائیة لمیاه الصزف الخام والمعالجة لمنطقة وادي سوف - حند, نصر الدين; غمام نواس, حمزة (Université of Eloued, 2018)
The objective of this work is to know some of the physiochemical properties of the raw and treated wastewater of three filter stations located in the Souf area, in the El-Oued province, where it was based on periodic laboratory analyzes carried out by the National sanitation office during the year 2017. The working principle of these three stations is based on the treatment with method of aerated lagoons. The obtained results showed that the stations performed a good and effective work, especially in the disposal of contaminants (MES, DBO5, DCO). The efficiency is different between these stations, and this is a result of different quality and quantity of water and technical factors. Also, comparing the results, we find that the second station (02) gives a good return compared to other stations. According to the obtained physiochemical results, the treated water characteristics of the stations studied are acceptable for national and international standards for the disposal of treated wastewater in the environment, while the characteristics of these water were in some way contrary to international and national standards for use in irrigation.
Master
Keywords: مياه الصرف ، التلوث ، محطة تصفية ، التحاليل الفيزيوكميائية; wastewater - pollution - water treatment - STEP - physico-chemical analysis.²